Optimizing pulsatile release of febuxostat for managing gout flares: a chronotherapeutic approach - Khyati Parekh; Vaishali Thakkar; Arjun Joshi; Chetan Sojitra; Saloni Dalwadi; Hardik Rana (SpringerOpen, 2023)
Abstract Background Chronic conditions such as nocturnal asthma, cardiac disorder, diabetes mellitus, joint pain and inflammation, and hypercholesterolemia necessitate a treatment strategy that can be planned in accordance with the disease's biological clock. The early morning spike in blood plasma uric acid was associated with gout. The treatment of these symptoms may not be feasible with immediate release formulations. Modified release formulations allow for controlled and consistent levels of medication in plasma throughout the day, but do not provide additional therapeutic levels when symptoms worsen. A chronotherapeutic system of febuxostat characterized by a time of no release (lag time) followed by a quick and complete release, can be designed to overcome this. The aim of the present study was to design a pulsincap of febuxostat to release the medication as per chronological conditions. Results The study commenced with the optimization of the capsule body coating to maintain its integrity over a 12-h period. Subsequently, polymers for immediate and sustained release tablets were screened, and the prepared tablets were subjected to physicochemical evaluation. For the optimization of the erodible plug, a 32 full factorial design was employed, leading to the creation of nine different polymer combinations. The response curves of HPMC K15M demonstrated a negative impact on swelling index and lag time, while displaying a positive effect on hardness. In contrast, the aloe vera, guar gum mixture exhibited significant effects on swelling index and lag time, but negatively influenced hardness. Diagnostic plots and ANOVA were utilized to confirm the significance and goodness of fit of the model. An optimized formulation was then developed based on the desirability plot. The formulated capsule, consisting of 91.71 mg of HPMC K15M and 101.56 mg of aloe vera, guar gum mixture, exhibited promising properties. Notably, it demonstrated a 70.69% swelling rate, a hardness of 5.78 kg/cm2, and an 8.57-h lag time. The pulsincap successfully met the requirement of immediate release within the first hour, followed by a pulsatile release with a lag time lasting for at least 8-10 h. Conclusions In conclusion, the formulation effectively reduces the threat of gout flares and enhances patient compliance due to its night-time dosing convenience.